Stoichiometric Conversion of Maltose for Biomanufacturing by In Vitro Synthetic Enzymatic Biosystems - Guowei Li; Xinlei Wei; Ranran Wu; Wei Zhou; Yunjie Li; Zhiguang Zhu; Chun You (BioDesign Research, 2022)
Maltose is a natural α-(1,4)-linked disaccharide with wide applications in food industries and microbial fermentation. However, maltose has scarcely been used for in vitro biosynthesis, possibly because its phosphorylation by maltose phosphorylase (MP) yields β-glucose 1-phosphate (β-G1P) that cannot be utilized by α-phosphoglucomutase (α-PGM) commonly found in in vitro synthetic enzymatic biosystems previously constructed by our group. Herein, we designed an in vitro synthetic enzymatic reaction module comprised of MP, β-phosphoglucomutase (β-PGM), and polyphosphate glucokinase (PPGK) for the stoichiometric conversion of each maltose molecule to two glucose 6-phosphate (G6P) molecules. Based on this synthetic module, we further constructed two in vitro synthetic biosystems to produce bioelectricity and fructose 1,6-diphosphate (FDP), respectively. The 14-enzyme biobattery achieved a Faraday efficiency of 96.4% and a maximal power density of 0.6 mW/cm2, whereas the 5-enzyme in vitro FDP-producing biosystem yielded 187.0 mM FDP from 50 g/L (139 mM) maltose by adopting a fed-batch substrate feeding strategy. Our study not only suggests new application scenarios for maltose but also provides novel strategies for the high-efficient production of bioelectricity and value-added biochemicals.